2015
DOI: 10.1097/shk.0000000000000352
|View full text |Cite
|
Sign up to set email alerts
|

TAT-HSP70 Attenuates Experimental Lung Injury

Abstract: Sepsis, a poorly understood syndrome of disordered inflammation, is the leading cause of death in critically ill patients. Lung injury, in the form of the Acute Respiratory Distress Syndrome (ARDS), is the most common form of organ injury in sepsis. The Heat Shock Response, during which Heat Shock Proteins (HSPs) are expressed, is an endogenous mechanism to protect cells from injury. We have found that the abundance of pulmonary Heat Shock Protein 70 (HSP70) is not increased following cecal ligation and double… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 47 publications
(55 reference statements)
1
6
0
Order By: Relevance
“…The heat shock response that induces HSP expression is an endogenous mechanism to protect cells from injury. The increase of HSP70 expression can be found during lung injury (Lyons, Raj, Chittams, Kilpatrick, & Deutschman, 2015). In our study, we also found that mRNA and protein levels of HSP70 in goat lung were increased after 2 hr transport.…”
Section: Discussionsupporting
confidence: 79%
“…The heat shock response that induces HSP expression is an endogenous mechanism to protect cells from injury. The increase of HSP70 expression can be found during lung injury (Lyons, Raj, Chittams, Kilpatrick, & Deutschman, 2015). In our study, we also found that mRNA and protein levels of HSP70 in goat lung were increased after 2 hr transport.…”
Section: Discussionsupporting
confidence: 79%
“…It is reported that the endogenous ligand HSP70 and HMGBI can activate TLR2 and TLR4 in the case of no pathogens, causing inflammation (11). HSP is a stress protein, as well as an endogenous protective material, and according to the molecular weight, it can be divided into HSP100, HSP90, HSP70, HSP60, HSP40 and small molecular weight HSP (26). HSP70 is a highly conserved protein expressed in the majority of organisms.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that HSP70 significantly decreased the inflammatory biomarkers, impaired apoptotic pathways via interactions with caspases, and improved outcome after septic and shock models of ALI in rats [34,35] . In this study, LPS caused a minor insignificant upregulation of HSP70 in lung tissues.…”
Section: Discussionmentioning
confidence: 99%